Novel approach of tackling wax deposition problems in pipeline using enzymatic degradation process: challenges and potential solutions - Saadon, Shazleen; Raja Abd Rahman, Raja Noor Zaliha; Ahmad Kamarudin, Nor Hafizah; Shahruddin, Sara; Mohd Shafian, Siti Rohaida; Ahmad Wazir, Norhidayah; Mohamad Ali, Mohd Shukuri (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Anthropogenic activities have led to hydrocarbon spills, and while traditional bioremediation methods are costly and time-consuming, recent research has focused on engineered enzymes for managing pollutant. The potential of enzymes for resolving wax flow problems in the petroleum industry remains unexplored. This paper offers a comprehensive review of the current state of research activities related to the bioremediation of petroleum-polluted sites and the biodegradation of specific petroleum hydrocarbons. The assayed enzymes that took part in the degradation were discussed in detail. Lipase, laccase, alkane hydroxylase, alcohol dehydrogenase, esterase, AlkB homologs and cytochrome P450 monooxygenase are among the enzymes responsible for the degradation of more than 50% of the hydrocarbons in contaminated soil and wastewater and found to be active on carbon C8 to C40. The possible biodegradation mechanism of petroleum hydrocarbons was also elucidated. The enzymes’ primary metabolic pathways include terminal, subterminal, and ω-oxidation. Next, given the successful evidence of the hydrocarbon treatment efficiency, the authors analyzed the opportunity for the enzymatic degradation approach if it were to be applied to a different scenario: managing wax deposition in petroleum-production lines. With properties such as high transformation efficiency and high specificity, enzymes can be utilized for the treatment of viscous heavy oil for transportability, evidenced by the 20 to 99% removal of hydrocarbons. The challenges associated with the new approach are also discussed. The production cost of enzymes, the characteristics of hydrocarbons and the operating conditions of the production line may affect the biocatalysis reaction to some extent. However, the challenges can be overcome by the usage of extremophilic enzymes. The combination of technological advancement and deployment strategies such as the immobilization of a consortium of highly thermophilic and halotolerant enzymes is suggested. Recovering and reusing enzymes offers an excellent strategy to improve the economics of the technology. This paper provides insights into the opportunity for the enzymatic degradation approach to be expanded for wax deposition problems in pipelines.